A hut too far: history of the Argentine Ventimiglia shelter on Peter I Øy. Issue 1 (1st January 2018) - Fontana, Pablo Gabriel
ABSTRACT: This paper addresses the barely known history of an Argentine Antarctic hut: the Teniente Luis Ventimiglia hut, installed by the Argentine Antarctic Institute on Peter I Øy (Peter I Island) in March 1971. In examining the history of the only Argentine Antarctic facility outside of the Argentine Antarctic Sector, this article describes the reasons behind the establishment of the hut and the scientific work that took place there as well as previous Argentine expeditions to Peter I.